Mouthwash with Active Oxygen (blue®m) Reduces Postoperative Inflammation and Pain - Bruna Marca Mattei; Soraia A. W. Imanishi; Grasieli de Oliveira Ramos; Paloma Santos de Campos; Suyany Gabriely Weiss; Tatiana Miranda Deliberador (Case Reports in Dentistry)
The aim of this case series was to evaluate the effects of blue®m mouthwash on oral surgical wounds. Eleven patients underwent bilateral preprosthetic surgery and were instructed to apply the product only to the right side of the surgery. In this way, the right side corresponds to the test side and the left side (place without applying any type of solution) to the control side. After seven days of using the product (3 times a day), the following parameters were evaluated by means of a visual analogue scale: pain, changes in taste, and acceptance by the patient. Then, the level of tissue inflammation was assessed, by the number of pixels, using ImageJ® software. The main results show that the blue®m mouthwash was widely accepted by patients, reducing their pain. The number of inflammation pixels was lower on the test side (p<0.05), indicating improved healing. It is suggested that blue®m mouthwash positively influences tissue healing reducing pain and the postsurgical inflammatory process; however, randomized clinical trials should be done to prove this clinical observation.